Role acmelogical culture in formation of intellectual nation (Journal of Philosophy Culture and Political Science, 2018)
A one of main goals of article is to reveal the role of acmeologic culture in formation of the intellectual nation.There were conducted research works in four higher education institutions of Almaty in order to identify the roleof acmeologic culture. The analysis of data is specifi ed in the paper. The analysis of data considers the role ofacmeologic culture in formation of the intellectual nation, likewise importance of the human capital and realizingof respondents.Key words: intellectual nation, intelligence, intellectual funds, capital, human capital, acmeology,acmeologic culture, intellectual society.